PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 22 PEKANBARU - Fitriani, Nurul; Wulandari, T. Ririn; Putri, Arsyisyah Adhadhini; Kurniaman, Otang; Noviani, Jumraul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the mathematics learning outcomes of fifth grade students of SD Negeri 22 Pekanbaru through the application of the Culturally Responsive Teaching (CRT) approach. This Classroom Action Research (PTK) was carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 22 fifth grade students. Data were collected through learning outcome tests and analyzed descriptively quantitatively. The results showed a significant increase in student learning completeness, from 36.36% in the pre-cycle to 59.09% in cycle I, and increased to 81,82% in cycle II. The students' average score also increased from 63 in the pre-cycle to 85.90 in cycle II. The application of the CRT approach proved to be effective in creating contextualized, meaningful learning, and actively involving students. This approach allows students to relate the subject matter to local culture, thus helping to understand concepts more deeply.